Linear Equation and Linear Function: An Alternative Material Based on Visual Representation in Mathematics - Sugama Maskar; Audra Pramitha Muslim; Darhim Darhim; Tatang Herman; Nicky Dwi Puspaningtyas (Jurnal Inovasi Matematika, 2024)
Linear equations and linear functions are important materials for students in developing their in-depth knowledge of arithmetic and algebra. However, there is a gap between potential development and actual development, which causes obstacles for students in understanding the concepts of these two materials. This gap results in other obstacles, including a fixed mindset in mathematics. The results of interviews with secondary school teachers in Indonesia also show that students have problems in number operations and motivation to learn mathematics. The design used in this study uses a descriptive qualitative study based on the results of literature studies, interviews with subject teachers, and the author's experience as an educator. This study also uses the theory of zone proximal development and mathematical mindset as a frame for preparing alternative material for equations and linear functions based on visual representations in mathematics. The results of this study contribute to providing alternative materials to reduce these barriers using a visual representation approach in mathematics. The author also provides alternative teaching arts to anticipate obstacles that arise when implementing mathematics material based on visual representation.